Increasing the frequency of breakfast consumption - Kothe, E.; Mullan, Barbara (Emerald Group Publishing Limited, 2011)
Purpose – A number of interventions aimed at increasing breakfast consumption have been designed and implemented in recent years. This paper seeks to review the current research in this area with the aim of identifying common features of successful interventions and strengths and weaknesses in the current research methodology. Design/methodology/approach – A systematic review of interventions aimed at increasing breakfast-eating frequency in a non-clinical sample was conducted. Findings – A total of 11 interventions were identified and reviewed; of these, only three resulted in an increase in breakfast consumption at follow-up. The three studies that were successful in changing breakfast consumption all included a psychosocial component that was successful in increasing positive attitudes towards nutrition in the intervention protocol. Many of the breakfast-eating interventions included in this review have methodological weaknesses, including difficulties in implementing interventions, small sample sizes, and selection biases, which future researchers should consider when designing and evaluating their own interventions. Research limitations/implications – These findings highlight the importance of including psychosocial components in interventions designed to increase breakfast consumption, while also signalling issues that should be addressed when designing and reporting future interventions. Originality/value – This review was the first to investigate the efficacy of interventions aimed at increasing breakfast consumption. The identification of weaknesses in the current body of research, and of successful and unsuccessful intervention practices is an important step in developing successful interventions in the future.